2017
DOI: 10.1002/lary.27008
|View full text |Cite
|
Sign up to set email alerts
|

Sino‐Nasal outcome test‐22 outcomes after sinus surgery: A systematic review and meta‐analysis

Abstract: Studies evaluating quality-of-life outcomes after sinus surgery using the SNOT-22 instrument universally show significant improvement after ESS. Across the published literature, the magnitude of change is quite variable and appears to be influenced by a number of factors including baseline SNOT-22 score, asthma prevalence, and length of follow-up. Laryngoscope, 128:581-592, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
77
1
3

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 94 publications
8
77
1
3
Order By: Relevance
“…found durable improvement in SNOT‐22 following FESS for CRS. Prior studies have found that patients with higher preoperative SNOT‐22 scores and a history of asthma demonstrate more improvement in their quality of life following surgery . This relationship of improvement to asthma did not reach statistical significance in our study.…”
Section: Discussioncontrasting
confidence: 90%
“…found durable improvement in SNOT‐22 following FESS for CRS. Prior studies have found that patients with higher preoperative SNOT‐22 scores and a history of asthma demonstrate more improvement in their quality of life following surgery . This relationship of improvement to asthma did not reach statistical significance in our study.…”
Section: Discussioncontrasting
confidence: 90%
“…Although the questionnaire may be a good resource for evaluating QOL in CF patients, it has not been validated for this purpose . As alluded to in the opening paragraph of the discussion, baseline SNOT‐20 scores in this cohort of patients are much lower than what is typically observed in standard CRS patients, in which average baseline SNOT‐22 scores are generally greater than 40 . This, in addition to the lack of a validated questionnaire to specifically target sinonasal QOL in the CF population, makes assessment of this patient population difficult, and highlights the importance of development of a sinus‐specific QOL instrument for use in the CF population.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, patients with eosinophil counts ≤10 per HPF had lower preoperative SNOT‐22 scores, and may have decreased ability for improvement as measured by SNOT‐22 scores. Preoperative SNOT‐22 scores have been recognized as an important factor influencing symptom score change following ESS . The presence of fibrosis, however, remained statistically significant in multivariable analysis, and preoperative SNOT‐22 scores were not different.…”
Section: Discussionmentioning
confidence: 91%